Postgraduate students’ experiences in interdisciplinary research studies - Winberg, C; Barnes, V; Ncube, K; Tshinu, S (South African Journal of Higher Education, 2011)
Many postgraduate interdisciplinary research (IDR) candidates in the applied disciplines work across two or more traditional areas of study. Such candidates often spend considerable time on knowledge-building activities outside their home (or undergraduate) disciplines; IDR candidates venture into new fields and are exposed to the cultures and values of different disciplines. In this study, IDR candidates, from different applied disciplines, were selected as case studies. The study was delimited to a range of interdisciplinary permutations across the ‘hard’ and ‘soft’ applied disciplines (e.g., engineering management, health informatics). The focus of this article is postgraduate students’ experiences in doing an IDR study for a Master’s thesis. In the article we explore the challenges faced by candidates, with a view to minimising these, given the contribution that IDR can make to a developing society.